PKM Aksi Penguatan Gizi Seimbang (PGS) Sebagai Upaya Peningkatan Keanekaragaman Konsumsi Pangan Pada Remaja Di Sman 1 Bangkinang - Lasepa, Wanda; Tri Hendarini, Any; Ananda Desti, Putri (Journal of Social and Community Service, 2022)
Adolescence is a period of transition or transition from childhood to adulthood marked by physical, psychological and psychosocial changes. According to the World Health Organization (WHO) the age group for adolescents is 12-24 years old. Fulfillment of nutritional needs during adolescence can maximize the work of the reproductive organs which will continue on to the products of conception. The Balanced Nutrition Guidelines aim to provide guidelines for daily food consumption and healthy behavior based on the principles of consuming a variety of foods, clean living habits, physical activity, and regular monitoring of body weight in order to maintain normal body weight. Diet is the most important behavior that can affect nutritional status. This is because the quantity and quality of food and drink consumed will affect nutritional intake so that it will affect the health of individuals and society. In order to keep the body healthy and avoid various chronic diseases or non-communicable diseases related to nutrition, people's diet needs to be improved towards balanced nutrition consumption. Good nutritional status can improve individual and community health.